Measuring assessors' experiences of grading marginal student performances in clinical assessments – The assess-safe tool: Development and preliminary psychometric validation. (February 2020) - Hughes, Lynda J.; Mitchell, Marion L.; Jones, Cindy; Johnston, Amy N.B.
Abstract: Assessment of fitness for practice in the nursing student population is an essential yet challenging component of nursing education. The aim of this research was to describe the development and preliminary validation of the Assess-Safe instrument that explores assessors' experiences of grading nursing student performances in clinical courses when that performance is not a clear pass or fail. A 3 phase approach was used to develop and psychometrically test the instrument. Phase 1 involved the development of a pool of items following a literature review, coupled with findings from qualitative data. In phase 2, an expert panel rated the items for clarity and relevance, reducing the item pool. Assessors of Australian undergraduate nursing students from industry and academia were recruited for this study. A sample of 149 assessors across industry and academia completed the resultant survey to pilot test the instrument; constituting Phase 3. A high content validity index score of 0.95 was achieved through expert review. Construct validity using factor analysis revealed four factors including: assessor support; process support; assessor introspection; and student support. The Assess-Safe instrument achieved good internal reliability with an overall Cronbach's alpha coefficient of 0.77; and sub-scale scores ranging from 0.71 to 0.79. The Assess-Safe instrument demonstrated satisfactory psychometric properties and has utility for education programmes, research and policy development across a variety of practice based professions. Nonetheless, further psychometric validation is warranted. Highlights: Assessors' experiences of grading student performances was explored. We developed and conducted preliminary validation of the Assess-safe instrument. Factor analysis revealed four factors with good internal reliability. Assessor introspection with assessor, process and student supports were revealed. The Assess-safe instrument is a first step towards understanding assessor concerns.